Risk Management and Ethical Perspectives in the Implementation of Artificial Intelligence (AI) in the Accounting Profession - Siregar, Zainal Arifin; Hasanah, Uswatun (Indonesia Auditing Research Journal, 2024)
The implementation of Artificial Intelligence (AI) in the accounting sector has provided significant opportunities to enhance efficiency and accuracy but also presents substantial ethical challenges related to integrity, accountability, and risk management. This study aimed to address three key questions: (1) How does AI impact integrity, data reliability, and the effectiveness of risk management in decision-making? (2) How are ethical responsibilities defined and applied in automated AI decision-making for risk mitigation? (3) What are the ethical implications of AI autonomy on risk management, human oversight, and the role of accounting professionals? A conceptual literature approach was employed to analyze these ethical challenges using Ulrich Beck's Risk Society Theory. The findings revealed that AI improved risk management efficiency; however, challenges such as algorithmic bias, lack of transparency, and privacy risks remained significant. Additionally, AI autonomy introduced ambiguities in accountability, necessitating human oversight and clear ethical frameworks. The study concluded that ethical AI implementation requires regulations supporting transparency, human supervision, and robust ethical guidelines to ensure alignment with professional values. These findings provide valuable insights for developing risk management and ethical practices in the application of AI within the accounting sector.